Internet downturn: finding valuation factors in Spring 2000 - Keating, Elizabeth K.; Lys, Thomas Z.; Magee, Robert P. (Journal of Accounting and Economics, 2003)
During Spring 2000, the Internet Stock Index declined 45%. Using a sample of internet firms, this paper investigates whether this decline was associated with new disclosures, such as earnings, analyst forecast revisions, and web-traffic measures, or to a “reassessment” by investors of pre-existing information. We find only modest evidence that the decline was associated with new disclosures. However, returns and post-decline stock prices are significantly explained by 1999 annual report data. When earnings are decomposed into gross profit and various expenses, traditional financial information contributes significantly more in explaining the cross-sectional returns and price levels than non-financial information.